PENGUJIAN REAKSI PASAR DAN INFORMASI FUNDAMENTAL TERHADAP RETURN SAHAM SEBELUM DAN SETELAH SK BAPEPAM âLK NO: KEP-431/BL/2012 - Endang Masitoh, Rochmi Widayanti (Prosiding Seminar Nasional, 2014)
The purpose of this study is (1) to examine market reaction of financial statementâs announcement and to know whether there is a big or small significant difference on Abnormal Return (relationship with before and after SK BAPEPAM-LK No. Kep-431/BL/2012; (2) to examine the influences fundamental information variables such as: earning and operating cash flow (OCF) and its influence to stock return (abnormal return). There are 36 sample manufacturing firms listed in the Jakarta Stock Exchange (BEJ) by means of purposive sampling method. The statistic method used to test hypotheses is paired sample test (market reaction from abnormal return) and linier regression with dummy variable. The result of this study indicates that the market reaction is not likely to be the same or different around each announcement date of the financial statements ofthe company both before and after the SK BAPEPAM-LK No: Kep-431/BL/2012. Furthermore, the results of research related to fundamental information in the form of earnings and operating cash flow, shows that earnings have a greater influence on abnormal returns, while operating cash flow no effect on the abnormal return. From these results it can be concluded that the investor or market still choose to use earnings in investment decisions.